Electromagnetic shielding property of carbon fiber felt made of different types of short-chopped carbon fibers - Liang, Jiyong; Gu, Yizhuo; Bai, Ming; Wang, Shaokai; Li, Min; Zhang, Zuoguang (Composites. Part A, Applied science and manufacturing, 2019)
Three types of short-chopped carbon fibers (SCF), including polyacrylonitrile based T300, M40J and pitch-based XN-90-60s, were used to prepare SCF felts by wet-laid method with hydroxyethylcellulos as adhesive. Electromagnetic interference shielding effectiveness (EMI SE) in X band was investigated using waveguide method. It is found that stirring treatment leads to higher damaging degree of XN90 than those of T300 and M40J. M40J SCF felt with areal density of 42.5 g/m2 exhibits the highest EMI SE value of 66.7–71.4 dB. Absorption is believed to be the dominant EMI shielding mechanism for SCF felt, because of obvious advantage in absorption effectiveness compared with reflection effectiveness. T300 and M40J SCF felts have larger fiber stacking density, more contact points, more integrated conductive network and larger inner surface area, which lead to excellent absorption effectiveness. It shows that the type of SCF is a key factor for designing and preparing SCF felts.